Polisens utvärdering av farliga hundar enligt lag (2007:1150) om tillsyn över hundar och katter - Westerlund, Johanna (SLU/Dept. of Animal Environment and Health (until 231231), 2011)

(untitled)
Aggression is a normal part of a dog’s behaviour repertoire and has always been an evolutionary relevant behaviour. Even if aggression in some contexts is relevant, it is one of the most common problem behaviour reported by dog owners. It has been discussed if some breeds are more likely to show aggression and therefore should be banned. On the 1st of January 2008 a new act was enforced by the Swedish government giving the police force greater authority in decisions to apprehend and euthanize dogs if they after an appropriate evaluation of the dog’s temperament think it is necessary. The aim of this report is to map out how an evaluation is done and if there is any room for improvement to be made. The results reveal that dogs of pitbull-and American staffordshiretype are overrepresented. The results also indicates that there is a difference in the judgement of the dog’s behaviour between two police precincts and that some of the words used to describe the dog’s behaviour were evaluative. To improve the quality of the evaluation of dangerous dogs the suggestion was given to standardise the test and the possibility to hand over the assessment to a independent party was considered.